When Protectors Become Spectators: A Review of Security Response to the March 2012 Communal Violence in Yendi, Northern Region of Ghana - Iddi, Z. (Ghana Social Science Journal, 2015)
The Dagbon conflict has been the subject of many academic discussions in the literature. However, the literature has focused more on the historical evolution of the conflict, as well as the recurring political interference in the conflict. Little attention, if any, has been paid to the role of government security agencies in the conflict. Using a desk study review of data, the study examined the omissions and commissions of the security agencies during the March 2002 communal violence in Yendi. The study found that lack of logistics, failure to retrieve weapons from private hands before the conflict, as well as several other security lapses contributed to the outbreak of the conflict and its outcome. The study concludes that the Yendi crisis exposed serious lapses in Ghana's government security architecture.
Ghana Social Science Journal, 12(1)
Keywords: Arms; Conflict; Dagombas; Factions; Intervention; Northern Ghana; Security reforms; Ya Na